A Meta-Analytic Approach to Swimming Performance Prediction: Reviewing Methods, Datasets, and Research Trends - Ari Tri Fitrianto; Muhammad Habibie; Parveen Kumar (Universitas Negeri Surabaya, 2025)
Background: Pico seems likely to be successful in competitive sports, particularly swimming, including the next Olympic swimming competition. The current manuscript offers a detailed insight into research on the prediction of swimming performance, between 2014 and 2024. Methods: This Swimming Performance Prediction research used the Systematic Literature Review (SLR) approach. Furthermore, to narrow down the articles relevant to research topics reviewed, this study adhered to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) when performing the systematic review. We find 21 journal publications from the representative studies for seeking identification and analysis for describing research topics or trends, datasets, techniques, methods, evaluations and problems in this research field. Results: The analyses presented provide detailed information on the topics and trends under investigation in the field of predictions for the prediction of swimming performance, reference to public datasets and the techniques and method often used in comparisons between researchers respectively. Conclusions: Swimming performance prediction plays an important role in improving training programs, guiding athlete selection, and evaluating progress.